2022
DOI: 10.1038/s41393-021-00737-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the changes in the microbiome following spinal cord injury: animal and human evidence

Abstract: Study design Systematic review. Objectives To investigate the changes in the microbiome among human and animal populations with spinal cord injury (SCI). Methods Four databases (EMBASE, Medline (Ovid), Web of Science, Cochrane Central Register of Trials (CENTRAL)) and Google Scholar were searched. No language restrictions were applied. Data extraction was done in parallel and independently by two reviewers. The sear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…In response to cornea injury, both diabetic and WT mice demonstrated changes in alpha diversity patterns compared to baseline. Such a response has been previously documented in other forms of severe non-abdominal injuries, including traumatic brain injury and spinal cord injury resulting in intestinal dysbiosis, which subsequently was followed by impaired systemic immunity ( 41 , 42 ). Such changes may represent a stress response resulting in a temporary alteration in gut microbiome composition.…”
Section: Discussionmentioning
confidence: 66%
“…In response to cornea injury, both diabetic and WT mice demonstrated changes in alpha diversity patterns compared to baseline. Such a response has been previously documented in other forms of severe non-abdominal injuries, including traumatic brain injury and spinal cord injury resulting in intestinal dysbiosis, which subsequently was followed by impaired systemic immunity ( 41 , 42 ). Such changes may represent a stress response resulting in a temporary alteration in gut microbiome composition.…”
Section: Discussionmentioning
confidence: 66%
“…According to the AMSTAR-2 criteria, 21 SRs [7,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] scored "critically low," 16 SR [13,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] scored "low," and 5 SR [36,[52][53][54][55] scored "moderate" (Figure 2). The most frequent drawbacks were as follows: no mentioning of the protocol in the systematic overview, no description of the rationale for the study designs included in the review, and no statement of funding for the included studies.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 99%
“…In the cecum and colon, CHC and MMT showed no significant difference, which indicated that the absorptive functions of CHC and MMT acted in the foregut rather than the hindgut. Second, CHC inhibited the abundance of Alistipes which is harmful bacteria related to causing intestinal inflammation in the ileum (Schirmer et al, 2019;Valido et al, 2022). This result suggested that although CHC had advantages in surface area and pore size, the function of absorption may also rely on other properties such as hydrophobic character, distances between porous sheets, and electrical conductivity (Nadziakiewicza et al, 2019).…”
Section: Discussionmentioning
confidence: 99%